KEKUATAN PEMBUKTIAN HASIL PEMERIKSAAN LABORATORIUM FORENSIK SEBAGAI ALAT BUKTI DALAM KASUS TINDAK PIDANA PEMBUNUHAN - Astrya Puspitasari; Diya Ul Akmal (Justitia et Pax, 2022)
Murder is a crime that both violates humanity and the law. Murders can be influenced by a variety of factors, including personal issues, economic hardships, and other concerns. The process of investigating murder cases necessitates the use of a Forensic Laboratory Examination to identify evidence and clues that will be used as legal evidence in court later. The aim of the research is to examine the role of evidence from Forensic Laboratory examination results in developing a judge's conviction in a murder case. This is a qualitative study that employs a normative legal method. The data used are secondary data gathered from literature studies and interviews at the National Police Headquarters Forensic Laboratory Center. In general, Forensic Laboratory examination results are utilized as evidence and instructions that can corroborate evidence. The Forensic Laboratory examination results can be utilized as documentary evidence (visum et repertum), expert testimonies, and evidence directives. The Forensic Laboratory investigation's findings are crucial in determining the judge's conviction, particularly in cases of murder. The judge's conviction must be founded on the fact that the defendant committed murder. As a result, the role of proving the Forensic Laboratory examination results is expected to guide the judge's conviction to get material truth. The expected implication is that the values of justice will be fulfilled in the Indonesian criminal justice system.